RESPONSIBILITY FOR THE SALES OF FAKE STAMPS ON TOKOPEDIA'S DIGITAL MARKETPLACE PLATFORM - Kelvin Adytia Pratama; Muhamad Amirulloh; Somawijaya Somawijaya (Jurnal Hukum Replik, 2020)
Today the internet has dramatically influenced business behavior by offering the opportunity to sell products of daily necessities directly to customers. In its development, the use of this technology sometimes tends to lead to negative things as well. One of them is the factual case of selling fake stamps on the Tokopedia digital platform. Based on this background, this research will discuss; First, regarding the legal qualifications of selling fake stamps on the Tokopedia digital platform. Second, related to the responsibilities of sellers and platforms regarding the sale of fake stamps on the Tokopedia digital marketplace. Both are based on the ITE Law and the Stamp Duty Law. This study used a normative juridical approach based on a law that is conceptualized as a rule or norm that becomes the benchmark for human behavior. The research specification used is descriptive analysis research specification. The data used is in the form of secondary data by reviewing literature and laws and regulations related to the sale of fake stamps and their correlation with the law of information technology and electronic transactions and stamp duty. By offering fake stamps on marketplace platforms, merchants, and e-commerce providers, namely the marketplace platform, are in effect breaking the law. Through the existing criminal law provisions, the seller/perpetrator must be held accountable for his mistake in accordance with the applicable sanctions. From the platform side, the various obligations that Tokopedia does not carry out in buying and selling activities cause problems, including the circulation of illegal goods on the platform, so that Tokopedia is obliged to be responsible.Keywords: E-Commerce; Platform; Information and communication technology; Stamp Duty.